The Effects of Social Media Content on a Firm’s Book-Based and Market-Based Performance: Literature Review - Naidanov, Ilia (Journal of Telecommunications and the Digital Economy, 2024)
The success of companies is increasingly dependent on their online image. Therefore, the research has called for a better understanding of the characteristics of a firm’s online content that can enhance a firm’s performance. This study delves into the impact of social media content on both book-based and market-based performances of firms, drawing insights from 32 articles published between 2016 and 2022. The present article encompasses the categorisation and explanation of the economic effects of user- and firm-generated social media content, while also exploring cross-firm and cross-industry spillover effects. The study extends prior research that has primarily focused on the effects of one type of content or the other and only on some specific measures. Moreover, the study visually illustrates the economic effects of social media content on book-based and marked-based firm attributes. These insights provide a valuable resource for firms seeking to optimise their social media strategies to improve performance and for researchers choosing a research agenda.